Complementary Therapies for Significant Dysfunction from Tinnitus: Treatment Review and Potential for Integrative Medicine. (20th September 2015) - Wolever, Ruth Q.; Price, Rebecca; Hazelton, A. Garrett; Dmitrieva, Natalia O.; Bechard, Elizabeth M.; Shaffer, Janet K.; Tucci, Debara L.
Abstract : Tinnitus is a prevalent and costly chronic condition; no universally effective treatment exists. Only 20% of patients who report tinnitus actually seek treatment, and when treated, most patients commonly receive sound-based and educational (SBE) therapy. Additional treatment options are necessary, however, for nonauditory aspects of tinnitus (e.g., anxiety, depression, and significant interference with daily life) and when SBE therapy is inefficacious or inappropriate. This paper provides a comprehensive review of (1) conventional tinnitus treatments and (2) promising complementary therapies that have demonstrated some benefit for severe dysfunction from tinnitus. While there has been no systematic study of the benefits of an Integrative Medicine approach for severe tinnitus, the current paper reviews emerging evidence suggesting that synergistic combinations of complementary therapies provided within a whole-person framework may augment SBE therapy and empower patients to exert control over their tinnitus symptoms without the use of medications, expensive devices, or extended programs.